IMPROVING ENGLISH LANGUAGE COMPETENCY BY USING SCIENTIFIC APPROACH FOR THE STUDENTS CLASS VIIIA.4 AT SMP NEGERI 1 SINGARAJA BASED ON CURRICULUM 2013 - ., Ni Km Ari Widyasih; ., Drs.Gede Batan,MA; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
IMPROVING ENGLISH LANGUAGE COMPETENCY OF THE STUDENTS OF CLASS VIII A.4 AT SMP NEGERI 1 SINGARAJA BY USING SCIENTIFIC APPROACH BASED ON CURRICULUM 2013 Abstract The study was conducted in order : 1.to improve the students English language competency by using a scientific approach at class VIII A.4 SMP Negeri 1 Singaraja; 2.to find out the students’ responses towards the implementation of scientific approach in teaching English language at class VIII.A 4 SMP Negeri 1 Singaraja. It involved 27 students as the subjects. It was conducted in a classroom action research design. Pre-test and pre-classroom observations were carried out before conducting the cyclic process. The classroom action was carried out covering five topics for five sessions. After the action was conducted, in only one cycle, the next cycle is observation consisting of: test, questionnaire, teaching learning process observation was done in particular to check the students’ attitudes and communicative ability. The data collection which belonged to the observation stage was conducted by using test, questionnaire, teaching learning process observation. The data were analyzed descriptively. The results of the study indicated that (1) the implementation of the scientific approach could improve successfully the students’ English language competency from 76.33 to 91.70 (cycle one) exceeded the passing grade. This finding is supported by the improvement of the students’ attitude quality, as well as the students’ positive responses towards the implementation of the scientific approach. Key-words: scientific approach, attitudes, English language competency. Kata Kunci : Key-words: scientific approach, attitudes, English language competency. IMPROVING ENGLISH LANGUAGE COMPETENCY OF THE STUDENTS OF CLASS VIII A.4 AT SMP NEGERI 1 SINGARAJA BY USING SCIENTIFIC APPROACH BASED ON CURRICULUM 2013 Abstract The study was conducted in order : 1.to improve the students English language competency by using a scientific approach at class VIII A.4 SMP Negeri 1 Singaraja; 2.to find out the students’ responses towards the implementation of scientific approach in teaching English language at class VIII.A 4 SMP Negeri 1 Singaraja. It involved 27 students as the subjects. It was conducted in a classroom action research design. Pre-test and pre-classroom observations were carried out before conducting the cyclic process. The classroom action was carried out covering five topics for five sessions. After the action was conducted, in only one cycle, the next cycle is observation consisting of: test, questionnaire, teaching learning process observation was done in particular to check the students’ attitudes and communicative ability. The data collection which belonged to the observation stage was conducted by using test, questionnaire, teaching learning process observation. The data were analyzed descriptively. The results of the study indicated that (1) the implementation of the scientific approach could improve successfully the students’ English language competency from 76.33 to 91.70 (cycle one) exceeded the passing grade. This finding is supported by the improvement of the students’ attitude quality, as well as the students’ positive responses towards the implementation of the scientific approach. keyword : Key-words: scientific approach, attitudes, English language competency.